2005
DOI: 10.1111/j.1365-2702.2005.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an osteoporosis prevention education programme for women in Hong Kong: a randomized controlled trial

Abstract: Osteoporosis was a serious health concern that most commonly affected women. As indicated by the results of this study, this educational programme can act as simple but effective nursing intervention to promote women's attitudinal and behavioural intentions towards osteoporosis-prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…In contrast to earlier tailored intervention studies, we did not find significant differences in behavior change between groups. 20,21,23 However, small sample size and nondifferential bias may have decreased our ability to detect significant differences in adherence to nutrition and exercise recommendations. Furthermore, the pilot intervention may be effective for improving knowledge and behavior maintenance, but may require refinements to effectively promote significant behavior change.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to earlier tailored intervention studies, we did not find significant differences in behavior change between groups. 20,21,23 However, small sample size and nondifferential bias may have decreased our ability to detect significant differences in adherence to nutrition and exercise recommendations. Furthermore, the pilot intervention may be effective for improving knowledge and behavior maintenance, but may require refinements to effectively promote significant behavior change.…”
Section: Discussionmentioning
confidence: 96%
“…Limited trials of osteoporosis risk reduction interventions have shown improved sustainability in behavior change and better adherence to osteoporosis prevention guidelines when such interventions are risktailored [20][21][22] or include patient education. 23,24 While these studies did not use the Internet as their modality, the Internet has capabilities suitable for delivering cost-effective tailored education materials to a wide variety of patient audiences. [25][26][27][28] Health interventions delivered via the Internet may also improve quality of clinical care while reducing health care spending.…”
Section: Introductionmentioning
confidence: 99%
“…Health education programmes have been shown to improve selfmanagement by increasing knowledge, physical activity and calcium intake and according to the European Union, might contribute to the promotion of lifestyle improvements (Compstone, 2004). Compliance with the suggested interventions has been evaluated for short periods, and the findings indicate that there is potential for lifestyle change after educational programmes for people with osteoporosis (Chan, Chung & Day, 2005;Laslett, Neil & Lynch, 2004;Sedlak, Doheny & Jones, 2000;Curry, Hogstel, Davis & Frable, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Pre-post and followup education data compared attitude and conception frequency before and after the education program. The study found that a targeted education program conducted on Hong Kong women resulted in significantly increased consumption of calcium including Soya-based foods, milk and vitamin D. 8 Osteoporosis is an established and well-defined disease that affects millions of people around the world and is a major cause of morbidity. Osteoporosis is a major public health threat for an estimated 44 million American or 55% of the people 50 years of age and older; in the US 10 million individuals are estimated to be already suffering from the disease and almost 31 million more are estimated to have low bone mass, placing them at increased risk for osteoporosis multiple compression fractures of the vertebrae resulting in skeletal deformity.…”
Section: Introductionmentioning
confidence: 99%